1969
DOI: 10.1063/1.1671675
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of the Decay Rate for Imprisoned 4.35-μ Spontaneous Emission in CO2

Abstract: Absence of quantummechanical effects on the mobility of argon ions in helium gas at 4.35 K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…At the densities of the pulsed experiments, considerable radiation trapping is expected for the V ) 1 f V ) 0 transition in this molecule. This phenomenon is well-known for CO 2 , and k 14 was determined by multiplying the reported 16 radiation-trapped rate for CO 2 by the factor of 4.8 noted above. The flow reactor experiments described above indicate that N 2 (V) quenching is very slow, even on Pyrex walls.…”
Section: Resultsmentioning
confidence: 98%
“…At the densities of the pulsed experiments, considerable radiation trapping is expected for the V ) 1 f V ) 0 transition in this molecule. This phenomenon is well-known for CO 2 , and k 14 was determined by multiplying the reported 16 radiation-trapped rate for CO 2 by the factor of 4.8 noted above. The flow reactor experiments described above indicate that N 2 (V) quenching is very slow, even on Pyrex walls.…”
Section: Resultsmentioning
confidence: 98%
“…The biacetyl formed via this pathway is designated k2 ; below it is shown that biacetyl (designated k1 ) is also formed via another pathway. The oxidation of acetyl radicals has been considered recently by several groups, , and the atmospheric oxidation of most of the other organic species is moderately well understood. ,
3 Reaction Mechanism for But-2-yne + HO in the Presence of O 2 • Reaction Channels Originating from e2
4 Glyoxal Formation from the Self-Reaction of Peroxyl Radical E2
…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…The biacetyl formed via this pathway is designated k2; below it is shown that biacetyl (designated k1) is also formed via another pathway. The oxidation of acetyl radicals has been considered recently by several groups, 23,[28][29][30] and the atmospheric oxidation of most of the other organic species is moderately well understood. 1,[25][26][27]…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…They make an important comparative pair because they are isoelectronic, have the same mass, and have similar vibrational frequencies. CO 2 has long been used in this role (see, for example, refs [1][2][3][4][5][6][7][8][9][10][11][12], but the studies of N 2 O began much more recently and are far less extensive. [13][14][15][16][17][18][19][20][21][22][23][24][25] Most experimental measurements have been confined to deactivation of both CO 2 and N 2 O excited to the (00 0 1) vibrational level of the asymmetric stretch mode, ν 3 .…”
Section: Introductionmentioning
confidence: 99%